Analytical Performance Study Of Explosively Formed Projectiles - G., Hussain; A., Hameed; J. G., Hetherington; A. Q., Malik; K., Sanaullah (Pleiades Publishing, Ltd., 2013)
Hydrocode simulations are carried out using Ansys Autodyn (version 11.0) to study the effects of the liner material (mild steel, copper, armco iron, tantalum, and aluminum) on the shape, velocity, traveled distance, pressure, internal energy, temperature, divergence or stability, density, compression, and length-to-diameter ratio of explosively formed projectiles. These parameters are determined at the instants of the maximum as well as stable velocity during the flight towards the target. The results of these parameters present the potential capability of each liner material used to fabricate explosively formed projectiles. An experimental analysis is performed to study the velocity status and the length-to-diameter ratio of explosively formed projectiles.